AKTIVITAS FISIK DAN TINGKAT DEPRESI LANSIA DI MASA PANDEMI - Yunita Sari (STIKes MERCUBAKTIJAYA, 2021)
COVID-19 has caused a pandemic in almost all parts of the world, including Indonesia. This has led to lockdown conditions in various countries. The Indonesian government is trying to break the chain of transmission of Covid-19, one of which is the Large-Scale Social Restriction (PSBB) which limits social and physical activities. One of the people affected by this policy is the elderly. Various studies have stated that physical activity will affect cognitive function and the level of depression in the elderly. The purpose of this study is to determine the relationship between physical activity and the level of depression in the elderly during a pandemic. This research is a descriptive corelative study with a cross sectional approach. Data were collected using A Physical Activity for the Elderly questionnaire to measure the physical activity in the elderly, and Geriatric Depression Scale to measure the level of depression. Bivariate statistical test using chi square. The results showed that there was no relationship between the level of physical activity and depression in the elderly during the pandemic (p value > 0.05).